Histone Acetylation Dynamics Integrates Metabolic Activity to Regulate Plant Response to Stress - Hu, Yongfeng; Lu, Yue; Zhao, Yu; Zhou, Dao-Xiu (Frontiers in Plant Science, 2019)
Histone lysine acetylation is an essential chromatin modification for epigenetic regulation of gene expression during plant response to stress. On the other hand, enzymes involved in histone acetylation homeostasis require primary metabolites as substrates or cofactors whose levels are greatly influenced by stress and growth conditions in plants. In addition, histone lysine acylation that requires similar enzymes for deposition and removal as histone acetylation has been recently characterized in plant. Results on understanding the intrinsic relationship between histone acetylation/acylation, metabolism and stress response in plants are accumulating. In this review, we summarize recent advance in the field and propose a model of interplay between metabolism and epigenetic regulation of genes expression in plant adaptation to stress.